Controlling the diameter of aligned single-walled carbon nanotubes on quartz via catalyst reduction time - Schweiger, Kai Manuel; Schaudig, Maximilian; Gannott, Florentina; Killian, Manuela Sonja; Bitzek, Erik; Schmuki, Patrik; Zaumseil, Jana (Carbon, 2015)
One of the main objectives of chemical vapor deposition (CVD) growth of single-walled carbon nanotubes (SWCNT) is control over their diameter and type (metallic or semiconducting). Here, we investigate the evolution of iron catalyst particles on quartz substrates depending on the duration of the reduction step with hydrogen and its effect on the growth of horizontally aligned SWCNT. We find a strong dependence of catalyst particle size and size distribution on the initial iron film thickness and the reduction time at 630 °C. Initial decrease of the particle size is followed by an unexpected increase. Statistical analysis of the Raman radial breathing modes of the SWCNT over large areas gave reliable and reproducible diameter distributions that correlated directly with the catalyst particle size distributions. By changing the reduction time it was possible to reproducibly shift the average SWCNT diameter from 1.5 (±0.3) nm to 1.2 (±0.2) nm while maintaining a nanotube density of 5-6 SWCNT/μm. In order to describe the evolution of the particle size during the reduction process at this particular temperature, we propose a model that includes the diffusion of iron into the quartz and its re-emergence.
Gesehen am 22.07.2020